Biodiversity of epizoic algae in the Mexican tropical Pacific - Quiroz González, Nataly; Aguilar Estrada, Luis Gabriel; Ruiz Boijseauneau, Ivette; Rodríguez Vargas, Deni Claudia (Instituto de Ecología, A.C., 2020)
Background and Aims: Although the phycological knowledge for the Mexican Pacific region is broad, most studies have been oriented to know the flora adhered to rocky substrates. However, the number of works on macroalgae that grow on living organisms, such as epizoics, is limited. The purpose of this paper is to contribute to the knowledge of epizoic algal flora in the Mexican tropical Pacific.Methods: Four samplings of the mollusk Chiton articulatus were carried out in two locations in Guerrero, Mexico, during 2014, to know the algae that grow on it. Furthermore, a literature review of studies in the Mexican tropical Pacific was carried out to obtain the records of the algae that grow on animals. Finally, algae on molluscs were determined by observations of complete thallus and sections.Key results: A total of 124 species, 81 genera, 51 families and 27 orders was reported, distributed in four algae divisions. The orders with the highest specific richness were Ceramiales (23) and Corallinales (20), and the families with the highest number of species were Rhodomelaceae (13), Cladophoraceae (11) and Lithophyllaceae (10). The most diverse genera were Amphiroa and Cladophora (7). For Guerrero, 12 new species records are presented, of which three are also new records for the Mexican tropical Pacific and three for the Mexican Pacific. The state with the highest number of recorded species was Guerrero (58). The most common substrate was mollusks. The predominant algal morphofunctional group were the filaments.Conclusions: The results of this work demonstrate that the biodiversity of algae present on animal substrates is high, contributing significantly to the specific richness recorded for Guerrero and the Mexican Pacific. The importance of developing more studies that focus on knowledge of algal epibiosis is evident.